Musik, Politik, dan Perdamaian dalam Film Biopik Bob Marley: One Love - Tanto Trisno (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2026)
This study examines the biopic Bob Marley: One Love (2024) as a cultural text that mediates the intersection of music, politics, and peace during Jamaica’s political polarization in the late 1970s. Using a qualitative approach, the research applies textual analysis, framing theory, and historical comparison to explore two main questions: (1) How does the film construct Marley’s role as a “mediator” in the PNP–JLP conflict, and to what extent does this align with historical records?; and (2) What are the aesthetic implications—mise-en-scène, montage, and sound design—in emphasizing symbolic reconciliation? Findings reveal that the film consistently frames Marley as a neutral figure advocating unity through music, culminating in the iconic gesture of joining Michael Manley and Edward Seaga’s hands during the One Love Peace Concert (1978). While the narrative remains faithful to the spirit of peace, it simplifies political complexities for dramatic effect. Aesthetic strategies—visual composition, rhythmic editing, and audio-vision—enhance the trans-sensory experience of reconciliation, reinforcing collective memory and cultural identity across generations.